Effects of Soil Moisture and a Mixed Culture of Photosynthetic Rhizobia and Bradyrhizobia on Reducing Sugars and Symbiotic Growth of Soybean - Jalil, Zainah (1998)
The main objective of this study was to observe the effect of soil moisture and mixed culture of photosynthetic rhizobia and bradyrhizobia on reducing sugars and symbiotic growth of soybean. Isolation of the native bradyrhizobia from Bungor, Kangkung, Katong, Lating, Lubok Kiat and Munchong series was conducted. One isolate from Lubok Kiat series was selected and labelled as UPMR48. Two separate experiments were conducted using photosynthetic rhizobia strains. The first experiment was a single inoculation of eight strains of photosynthetic rhizobia to soybean. Two strains (MKAa2 and MKAaJ) were found capable of forming root nodules. In the second experiment, photosynthetic rhizobia strains (MKAa2 and BT Ai 1 ) were inoculated to soybean as a single or mixed culture along with bradyrhizobial strains (UPMR48, TAL I 02 and CB 1 809). The best mixed culture was MKAa2 and UPMR48 strains. Nodulation and growth patterns of soybean experiment was conducted with plants harvested at different plant age, 28 days (D28), D35, D42 and D49, after planting. Maximum nodulation was observed at D42 (early pod filling stage). The Water Level experiment was conducted using peat and mineral soil with a control soil moisture maintained at field capacity and water levels maintained at 7.5 em. 1 5.0 em, 20.0 cm, 25.0 em, 30.0 em (peat) and 7.5 em, 15.0 em, 22.5 cm, 30.0 cm (Lubok Kiat series) from the soil surface. Plants were harvested at D32 and D42 for peat and Lubok Kiat series, respectively. Maximum plant growth and nodulation were observed in conditions with water levels at 25 cm (peat) and 30 cm (Lubok Kiat series) from the soil surface; the soil moisture was at or above the field capacity (pF 2.0-2.5). In peat, root nodules were abundant at nearest to the maintained water level for all treatments while for Lubok Kiat at the initial 0-7.5 cm depth of soil surface irrespectively of the water level treatments.